Tourism, Cultural Heritage and Social Sustainability: The Mediating Role of Hospitality in Island Territories - Duarte de Almeida, I. (13.ª Conferência MIIS | Património Cultural, Turismo e Sustentabilidade Social, 2026)
Tourism has become one of the most significant drivers of economic and social transformation in contemporary societies, particularly in territories that depend heavily on this activity. At the same time, its rapid expansion has raised growing concerns about environmental pressures, social imbalances, and the preservation of cultural heritage. In this context, the role of the hotel industry extends beyond providing accommodation. Hotels operate at the intersection of tourists, local communities, and territories, positioning themselves as key actors in mediating the relationship among tourism development, cultural heritage, and social sustainability. Focusing on the case of Madeira, this study explores how sustainability practices are being implemented in the hotel sector and how they contribute to broader processes of territorial and social balance. Based on a qualitative approach, supported by semi-structured interviews with hotel managers, the research analyses not only the environmental dimension of these practices, but also their implications for local integration, cultural valorisation and stakeholder engagement. The findings suggest that sustainability in hospitality is not limited to environmental efficiency or cost reduction. Rather, it is increasingly associated with the valorisation of local resources, the integration of regional supply chains and a growing awareness of cultural identity. Hotels tend to incorporate local products, traditions and practices into their operations, thereby contributing, directly and indirectly, to the preservation and promotion of cultural heritage. At the same time, these practices influence tourist behaviour, encouraging more responsible consumption patterns and fostering closer connections with local communities. More than a set of operational measures, sustainability emerges as a relational and strategic process that helps shape more balanced tourism models. In this sense, the study highlights the importance of understanding hospitality not only as an economic activity but also as a space of interaction where tourism, cultural heritage, and social sustainability are continuously negotiated and redefined.